The Use of Technology for Autonomous Language Learning outside the Classroom - Maratkyzy, A.; Bakbergen, A.; Zhandarbek, М. (M. S. Narikbayev KAZGUU University School of Liberal Arts, 2023)
Autonomous Language Learning (ALL) is a process when students take control over their language learning outside the classroom. The paper is dedicated to the use of technology for ALL outside the classroom and the aim of the paper is to investigate ALL in Kazakhstan based on the example of one Kazakhstani university students’ experience. After data collection, which was done with the help of a questionnaire, data analysis was carried out through various tests to identify correlations between different variables related to possible answers and evidence for the research questions and hypotheses. Bivariate correlations, chi-square, Spearman's Rho, t-test, Pearson's R, Likert scale question reliability test were conducted. The results revealed that watching videos in the original language, improving certain language skills, self-monitoring the learning process, communicating with native speakers, successfully passing tests and getting good grades were cited as advantages of ALL. The disadvantages, on the other hand, included inaccessibility of feedback, difficulty in choosing from a wide range of materials, difficulty in disciplining oneself in the learning, absense of guidance from the teacher, and finding materials at the appropriate level. It is worth noting that the most common shortcoming was that students could not get feedback from teachers in ALL. It was confirmed that there was a connection between the usage of various technologies and the mastery of certain skills. The study proved that technology is an important factor in ALL. More and more activities and tasks require the use of technology to solve problems, and students reported using a wide range of electronic materials and digital tools for independent learning
Keywords: autonomous language learning, use of technology outside the classroom, English, foreign languages